Hydrological dynamics, wetland morphology and vegetation structure determine riparian arthropod communities in constructed wetlands - David Åhlén; Sofia Hedman; Jerker Jarsjö; Björn K. Klatt; Lea D. Schneider; John Strand; Ayco Tack; Imenne Åhlén; Peter A. Hambäck (Basic and Applied Ecology)
Wetland hydrological dynamics often dictate the composition of biological communities found in or near wetlands, either directly or through changes in vegetation composition. However, much remains unknown, particularly regarding how riparian arthropods respond to such dynamics. In this study, we used high-resolution hydrological data, along with presence of grazing livestock and shoreline vegetation height from 41 constructed wetlands in south-western Sweden to explore flood zone areas, flood frequencies, vegetation and grazing as drivers of the resident arthropod communities. The collected material consisted of 26,817 arthropods, where the dominant groups were Diptera (13,258 specimens), spiders (6,207) and Coleoptera (2,858), which were collected using SLAM (Sea Land and Air Malaise) trapping, along with pitfall trapping and vacuum sampling of riparian arthropods. We found group-specific responses to inundation frequencies, where wetlands with higher frequencies had lower abundances of some beetles and tipulids, and where wetlands with longer low-water table periods contained less trichopterans and heteropterans. In contrast, the size of flood zone areas only affected some wolf spider groups, that were more abundant in wetlands with intermediately sized flood zones. Shoreline vegetation height affected multiple groups, spiders, beetles and dipterans, but in different directions, whereas presence of grazing livestock had limited impact on abundances and community compositions. Given the variable responses to wetland hydrological and structural drivers, it seems that wetland arthropod communities would benefit from a high local wetland habitat variability, or wetlandscapes where individual wetlands have differing hydrological dynamics, morphology and vegetation.